Disaster-prevention Measures for Underground Space to Deal with Large-scale Earthquakes and Intensified Flood Disasters in Japan. (2016) - Niira, Kyoko; Shigeno, Katsutoshi; Kikuchi, Masahiko; Inoue, Tadashi
Abstract: In Japan, underground spaces have been developed, mainly large-scale terminals in urban districts. These underground spaces need various disaster-prevention measures in order to deal with flood due to frequent torrential rains in addition to Tokyo Inland Earthquake and Nankai megathrust earthquake, which possibly will happen in the near future. Most owners or managers of underground spaces are the private sectors. They conduct repairs of the facilities and improvement of the equipment, having technical and financial support from the national and local governments so that the facilities and equipment meet standards of laws. Moreover, they advance disaster-prevention measures such as regular evacuation drills. Furthermore, Japan is to held Tokyo Olympic and Paralympic Games in 2020. It is expected that many people from within the country and abroad will visit various places in Japan including Tokyo and use underground spaces. Therefore, whether in normal times or emergency, improvement of facilities for better accessibility and highly accurate guide system using devices including smart phone are being conducted by joint effort of the public and private sectors so that large numbers of general public will be able to use underground spaces in peace. Here we report the latest efforts for underground spaces in Japan.